Lipid and blood pressure lowering potential of Mikania micrantha through enzymatic inhibition - Shafie, Nurul Husna; Ishak, Amirah Haziyah; Mohd Esa, Norhaizan; Bahari, Hasnah (MDPI, 2020)
Mikania micrantha Kunth (Asteraceae) is a plant that traditionally used to reduce the risk of hyperlipidemia and hypertension. This study was aimed to examine the in vitro potential of different parts of M. micrantha (leaves and stems) extracts to inhibit enzymes relevant to hyperlipidemia i.e., pancreatic lipase (PL), lipoprotein lipase (LPL) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR), and also hypertension i.e., angiotensin-I converting enzyme (ACE). The inhibitory activities of hot water, cold water, 70% ethanol and ethyl acetate extracts of the leaves and stems of M. micrantha against the enzymes were determined spectrophotometrically using PL, LPL, HMGR, and ACE inhibition assays. The ethanol stems (ETS) extract exhibited the highest PL inhibitory activity (IC50=4.49±2.50 μg/mL) and showed no significant (p > 0.05) difference with orlistat (IC50=0.31±0.01 μg/mL). The ethanol leaves (ETL) extract showed the highest LPL (IC50=1.42±0.48 μg/mL) and HMGR inhibitory activities (50.12±3.44%). Hot water stems (HWS) showed the greatest ACE inhibition (97.47±1.19%), but not significant (p > 0.05) when compared to other extracts and captopril (98.42±0.93%). Overall, all extracts exhibited remarkable inhibitory activity against PL, LPL, HMGR, and ACE. This study demonstrated the potential of M. micrantha extracts as anti-hyperlipidemic and anti-hypertensive agents.